Rules and ethics : perspectives from anthropology and history - Clarke, Morgan; Corran, Emily (Manchester University Press, 2021)
This book provides a new, interdisciplinary perspective on the importance of detailed rules to many of the world's ethical traditions. A valuable theoretical introduction sets the agenda for a series of comparative studies, spanning pre-modern Hindu ethics, Classical Rome and Christian casuistry, contemporary Judaism and the Islamic sharia.